(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Industrial sector is gradually playing a more important role in Bangladesh economy and EPZs have provided a good platform of industrial establishment. Dhaka EPZ since its establishment has altered the fragile environment of the surrounding area. Huge amount of effluents discharged from Dhaka EPZ has been polluting the surface and groundwater. Surface water contamination by industrial effluents released from Dhaka Export Processing Zone (DEPZ) and the ramification to groundwater have been estimated. The study involves analyzing physicochemical properties along with major Anionic contaminants in waste water samples. Conversely their potential transmission into groundwater has been evaluated by analyzing HTW water samples from the surrounding area. Some important physical parameters were measured while collecting the sample in field condition. The suite of 6 major anions (F-, Cl-, NO2-, NO3-, SO4-2 and HCO3-) have been measured in ppm level of concentration by analyzing with chemically suppressed Ion Chromatograph while HCO3- content was determined by Titration method. Analysis reveals pH maximum 9.55, DO maximum 2.40 mg/L, TDS maximum 1280 mg/L, Bi-carbonate maximum 891 mg/L, Sulfate maximum 452 mg/L, Chloride maximum 179 mg/L, Nitrate maximum 44 mg/L and Fluoride not above detection limit. Higher concentration of Cl-, SO4-2, NO3- in waste water samples compared to the standard by DOE (Department of Environment) as well as background concentration from uncontaminated water can be correlated with industrial effluent discharge. On the other hand low level of concentration found in groundwater samples indicates that groundwater is still safe. This phenomenon is explained by the presence of impervious clay layer. Key words: Dhaka EPZ; Effluent; Madhupur Tract; Contaminants; DOE; Environment; Clay layer DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8181 Bangladesh J. Sci. Ind. Res. 46(2), 153-162, 2011